2010
DOI: 10.1159/000319257
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Corticotropin-Releasing Factor, Urocortin and Citalopram in a Primate Model of Stress-Induced Amenorrhea

Abstract: Background/Aims: We established a cynomolgus macaque model of stress-induced amenorrhea in which the application of combined metabolic and psychosocial stress suppressed ovulation in stress-sensitive (SS) individuals, but not in highly stress-resilient (HSR) individuals. We previously reported that SS monkeys have deficits in global serotonin release and serotonin-related gene expression in the raphe nucleus, and that administration of the selective serotonin reuptake inhibitor S-citalopram increased estrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 108 publications
2
36
1
Order By: Relevance
“…In humans, estrogen alterations due to menopause and the menstrual cycle are associated with transient alterations in brain structure [152,153]. Moreover, primates who are sensitive to stress-induced amenorrhea exhibit greater evidence of CRH activity in the paraventricular nucleus and thalamus and high CRH fiber density in the central nucleus of the amygdala than resilient animals [154]. These exposures which are of a relatively small magnitude strongly suggest that in humans, as in rodents, the massive hormonal changes of pregnancy alter brain function and morphology.…”
Section: Maternal Programmingmentioning
confidence: 99%
“…In humans, estrogen alterations due to menopause and the menstrual cycle are associated with transient alterations in brain structure [152,153]. Moreover, primates who are sensitive to stress-induced amenorrhea exhibit greater evidence of CRH activity in the paraventricular nucleus and thalamus and high CRH fiber density in the central nucleus of the amygdala than resilient animals [154]. These exposures which are of a relatively small magnitude strongly suggest that in humans, as in rodents, the massive hormonal changes of pregnancy alter brain function and morphology.…”
Section: Maternal Programmingmentioning
confidence: 99%
“…Since citalopram is a selective serotonin reuptake inhibitor, we examined its efect on serotonin-related gene expression (Lima et al, 2009). In addition, due to the involvement of the CRF system in stress and the link between serotonin and CRF, we examined CRF and UCN1 innervation of the serotonin system (Weissheimer, 2010) and CRF-R2 expression in the dorsal raphe.…”
Section: Overview and Correlationsmentioning
confidence: 99%
“…It is also noteworthy that stress-sensitive animals exhibited reduced serotonin gene expression, elevated CRF in the PVN and higher CRF fiber density in the dorsal raphe nucleus in the absence of external stress (Centeno et al, 2007, Bethea et al, 2008, Weissheimer, 2010). There are numerous studies in humans indicating that childhood trauma leads to vulnerability to stress and affective disorders in adulthood (Nemeroff, 2004a), Since the cynomolgus monkeys are caught and imported, we speculate that the vulnerability of some individuals may be due to “childhood trauma” in the wild such as variable foraging demands on the mother or abuse (Coplan et al, 2010).…”
Section: Overview and Correlationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest (i) that mechanisms accounting for the antidepressant and anti-dyskinetic effects of citalopram may be partly different, (ii) that the anti-dyskinetic effect of SSRIs in PD patients may require doses of these drugs that are higher than those used to treat symptoms of depression. Indeed, a previous study showed that in female monkeys a dose of 1.2-4.8 mg/kg of citalopram given for 15 weeks elevated blood levels of this drug into the therapeutic range for treating depression in humans (Lima et al, 2009;Weissheimer et al, 2010). Although citalopram was only given acutely in our study, the effective dose, 15 mg/kg, seems to be higher than the dose needed to treat depression; however, we cannot discard the possibility that citalopram may become effective at lower doses when given chronically in the MPTP-treated macaques.…”
Section: Discussionmentioning
confidence: 99%